Leukemic transformation and second cancers in 3649 patients with high-risk essential thrombocythemia in the EXELS study. (November 2018) - Birgegård, Gunnar; Folkvaljon, Folke; Garmo, Hans; Holmberg, Lars; Besses, Carlos; Griesshammer, Martin; Gugliotta, Luigi; Wu, Jingyang; Achenbach, Heinrich; Kiladjian, Jean-Jacques; Harrison, Claire N.
Highlights: Essential thrombocythemia (ET) has a risk of malignant transformation. We determined transformation to acute myelogenous leukemia (AML). Standardized incidence ratio of AML was high in ET patients on hydroxycarbamide. No cases of AML occurred in ET patients treated with anagrelide. Rates for non-AML cancers were similar in the two groups. Abstract: EXELS, a post-marketing observational study, is the largest prospective study of high-risk essential thrombocythemia (ET) patients, with an observation time of 5 years. EXELS found higher event rates of acute leukemia transformation in patients treated with hydroxycarbamide (HC). In the current analysis, we report age-adjusted rates of malignant transformation from 3460 EXELS patients exposed to HC, anagrelide (ANA), or both. At registration, 481 patients had ANA treatment without HC exposure, 2305 had HC without ANA exposure, and 674 had been exposed to both. Standard incidence ratios (SIRs) were calculated using data from the Cancer Incidence in Five Continents database to account for differences in age-, gender-, and country-specific background rates. SIRs for acute myelogenous leukemia (AML) were high in ET patients. SIRs for AML were high in HC-treated patients, but AML was rare in ANA-treated patients; no cases of AML were found in patients only treated with ANA. No statistically significant difference was seen between SIRs for ANA and HC treatment for AML or skin cancer. SIRs for other cancers were similar in the HC and ANA groups and close to 1, indicating little difference in risk. Although statistically inconclusive, this study strengthens concerns regarding possible leukemogenic risk with HC treatment. (NCT00202644)